Slavs on Steamships. Steamship Travels between Europe and Asia, 1869–1890 - Ewertowski, Tomasz (Poznańskie Studia Slawistyczne, 2022)
This article examines diverse travel narratives about steamship voyages to Asia in the first two decades after the opening of the Suez Canal, with special focus on journeys through the Suez Canal, Red Sea, and Indian Ocean. Sources include Polish, Serbian and Russian authors: Julian Fałat, Vlado Ivelić, Lucjan Jurkiewicz, Milan Jovanović, Vsevolod Krestovskiy, Karol Lanckoroński, Bronisław Piłsudski, Paweł Sapieha, Henryk Sienkiewicz, Ivan Yuvachev, Hugo Zapałowicz, and Ivan Zarubin. Given this variety of sources, consisting of 12 accounts in 3 languages, written by different types of travellers with dissimilar social backgrounds, it is possible to demonstrate a variety of phenomena that may be associated with steamship voyages. The two main issues examined here are: 1) the coexistence of multiple mobilities in the era of steam power, 2) different experiences of time while voyaging.